If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 + -2x = 23 Reorder the terms: 7 + 5x + -2x = 23 Combine like terms: 5x + -2x = 3x 7 + 3x = 23 Solving 7 + 3x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = 23 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 23 + -7 3x = 23 + -7 Combine like terms: 23 + -7 = 16 3x = 16 Divide each side by '3'. x = 5.333333333 Simplifying x = 5.333333333
| m+2n+-2m+3n=0 | | 12x^2y^5= | | (k-1)(x^2+kx+1)=0 | | -2y-1.7=2.3 | | 2x+6y=12y | | -x=.77 | | (2x^2-9x)(2x^2-9x+13)+36=0 | | (2x^2-9x)(2x^2-9x+13)=-36 | | 5y+11x=87 | | 3x=7(7+1) | | 14(x-3)=112 | | (x+7)+(5x-7)+(4x)=180 | | (7x-4)+(3x+8)+(x)=180 | | 4y-37=99 | | 4y-25=79 | | 4y-25=101 | | 6x-40=110 | | -15-x=-17 | | a+4b-3a-2b= | | 4x-12=96 | | 4+12=96 | | 2(u+2)-8u=28 | | -8v+5(v-7)=-20 | | 1y-.75=.5y-9 | | =ax+ay+az | | -77-3=11 | | e^3x(p-1)+p^3e^2y=0 | | 4k+8= | | (3y+12x)(8y-9x)=152 | | X^2+x^3=11-x | | 5x+x=39 | | -14+6b+7-2b=1+b+5b |